Real-Time Experimental Comparison of Two Depth Control Schemes for Underwater Vehicles. (20th February 2015) - Maalouf, Divine; Creuze, Vincent; Chemori, Ahmed; Tamanaja, Ivan Torres; Mercado, Eduardo Campos; Muñoz, Jorge Torres; Lozano, Rogelio; Tempier, Olivier
This paper deals with an experimental comparison between the proportional integral derivative (PID) control law and the adaptive nonlinear state feedback control, both applied on the AC-ROV underwater vehicle. The experimental results evaluate the closed-loop behaviour of the system under each controller in various operating conditions in order to compare how robust they are towards parameters' change and how they can reject external disturbances. It was concluded that the adaptive controller ensures a faster convergence and can adapt to a change of parameters as well as compensate for external disturbances. The PID needs to be retuned for every parameter change and is more sensitive to external disturbances.